Review of computerized decision support systems for oral anticoagulation management. - Fitzmaurice, D; Hobbs, F; Delaney, B; Wilson, S; McManus, R (1998)
Computerized decision support systems (CDSS) are available to assist clinicians in the therapeutic management of oral anticoagulation. We report the findings relating to CDSS for oral anticoagulation management of a primary-care-based systematic review which largely focused on near-patient testing. Seven papers were reviewed which covered four different systems. The methodology of these papers was generally poor, although one randomized controlled trial showed improved therapeutic control associated with computerized management compared with human performance.